As heurísticas do effectuation e suas consequências para o empreendedor - Massa, Rubens Mussolin (2020)
A theory of effectuation is based on the entrepreneur's decision process, comprising an effort to seek a method capable of guiding the discovery and realization of opportunities. An effectual logic subverts the principles of entrepreneurial models that use the principle that, in order to seek the future in advance, they seek to build it step by step, in a process of co-creation between entrepreneur and environment, seeking or learning constantly in interaction without be concerned with gathering the ideal conditions for this, and offer a means of control in this process. At the center of this process, the human being with his qualities and imperfections. It is widely known, especially by neuroscience, that the decision-making process is not entirely rational, with several variations inherent to it. Among them, the use of heuristics, or shortcuts, which on the one hand make it more difficult to think because it simplifies reality, on the other hand it can lead to decision errors, due to cognitive problems, also discussed in the business and enterprise literature. This paper argues that the effectuation theory, proportionally “pocket rules”, which serves to guide the entrepreneurial decision-making process, uses heuristics, as mentioned above and demonstrated in the literature on micro-foundations, affected or the final result of the lending process. An investigation proposed in this objective thesis comprises how to choose the use of heuristics through the entrepreneur's action and decision logic that affects cognitive injuries, seeking to discuss how these effects affect or result in a final contribution to success or not to performance. The work contributes to the advancement of theory, paying attention to the incipient field of micro-foundations associated with the logic of decision-making and its consequences, seeking to understand, how it is possible to infer heuristics, or pocket rules, which corroborate with the professional process, it is possible to find in the future a logic of errors and benefits associated with the use of one of the polar processes proposed in the theory of effectiuation and validate the empirical form of some premises. Empirical tests were used in real entrepreneurs and the search for possible relationships between heuristics suggested by the Effectuation theory, an incidence of cognitive effects and variables that are used in the literature as important in this research. The results show that part of the hypotheses were accepted, and therefore there is a relationship between the use of heuristics and cognitive effects, with emphasis on a relationship between control effects and the use of heuristic causes.